Narrative Finance - The use of narrative to inform investment judgement. How stories move markets - the system behind the Boeing 737 MAX shock news. - Harris, Richard (Cranfield University, 2023)
NARRATIVE FINANCE: The use of narrative to inform investment judgement Narrative Finance is the term coined for research into this new sub-discipline of financial economics - for it is the “voice of the market.” The information embedded within text and speech is pervasive in determining asset prices. This contribution to financial research highlights ways to use financial narratives to inform investment judgement. Financial narrative is modelled as a disruptive force by uniquely applying General System Theory to illustrate the complex architecture of the financial system. The energy budget of a material narrative is seen to be expended in the work carried out to adjust asset prices. Investors can use the departure and recovery of prices from the dynamic equilibrium upon the receipt of news as an investment indicator; described herein as Decoupling Theory. The signal of a narrative is mapped as it travels through the non- linear financial system (and back as feedback). Narrative nomenclature is devised to describe dominant, dormant, and legacy narratives, the Narrative Cycle, Narrative Signal, Narrative Phases, and the Narrative Tree. This theory was tested against the shock news of the two Boeing 737 MAX 8 accidents, which provided two proxy narrative signals and investment outcomes from a single event cause. The empirical output includes the proof of theory for the narrative morphology and phases, the extraction of fast and frugal investment narrative indicators, the importance of feedback, and the matching of narrative frequency to market movements. These metrics can help investors make better judgements and decisions by narrowing the probabilities in nowcasting and forecasting models. Narrative Finance is an intellectual descendant of classical finance and behavioural economics and contributes an alternative method of valuing investments to the toolbox of investors, academics, and securities regulators.
Belghitar, Yacine - Associate Supervisor
Keywords: Narrative Finance; news; narrative; events; financial system; financial economics; narrative signal; investment indicators; negative system feedback; positive system feedback; shock news; legacy narrative; financial energy; narrative cycle; narrative phases; asset price; price adjustments; narrative decay; General Systems Theory; case study; event study; Boeing, 737 MAX; scenario planning; probabilities; nowcasting; forecasting; stock market; sentiment; machine learning; linguistics; Decoupling Theory